The Topp-Leone odd log-logistic family of distributions - Brito, E.; Cordeiro, G. M.; Yousof, H. M.; Alizadeh, M.; Silva, G. O. (Journal of statistical computation and simulation, 2017)
We introduce a new class of continuous distributions named the Topp-Leone odd log-logistic family, which extends the one-parameter distribution pioneered by Topp and Leone [A family of J-shaped frequency functions. J Amer Statist Assoc. 1955;50:209-219]. We study some of its mathematical properties and describe two special cases. Further, we propose a regression model based on the new Topp-Leone odd log-logistic Weibull distribution. The usefulness and flexibility of the proposed family are illustrated by means of three real data sets.